Paradigma Pembangunan Ekonomi Konvensional dan Pembangunan Ekonomi Islam - Erni Yusnita Siregar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research is entitled the different paradigms of conventional economic development and Islamic economic development. The background of this research is that there are differences between Islamic economics and conventional economics in the field of development both from the aspects of methodology, principles, principles and scope. For this reason, researchers conducted a literature study on the differences in the paradigms of conventional economic development and Islamic economic development. The method used is descriptive analysis method, which is a method that examines the status of human groups, objects, conditions, a system of thought, or a class of events at the present time with the aim of making systematic, factual and accurate descriptions, drawings or drawings of facts, nature, as well as the relationship between the phenomena investigated. So this study resulted in findings that: the paradigm (worldview) that underlies Islamic development economics is different from conventional economics. Islamic development economics is formed based on the Islamic worldview which places the main guide in carrying out life activities (including economic activities both individually and as entities or groups) originating from the Al-Qur'an and Al-Hadith. Conventional development economics has fundamental differences with Islamic development economics. Conventional development economics has not been able to fully meet the needs of Islamic society in terms of knowledge, fulfillment of basic needs, and accommodating the basic motives of economics so that the presence of Islamic economic development is indispensable